5w+6=9w+3

Simple and best practice solution for 5w+6=9w+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5w+6=9w+3 equation:


Simplifying
5w + 6 = 9w + 3

Reorder the terms:
6 + 5w = 9w + 3

Reorder the terms:
6 + 5w = 3 + 9w

Solving
6 + 5w = 3 + 9w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-9w' to each side of the equation.
6 + 5w + -9w = 3 + 9w + -9w

Combine like terms: 5w + -9w = -4w
6 + -4w = 3 + 9w + -9w

Combine like terms: 9w + -9w = 0
6 + -4w = 3 + 0
6 + -4w = 3

Add '-6' to each side of the equation.
6 + -6 + -4w = 3 + -6

Combine like terms: 6 + -6 = 0
0 + -4w = 3 + -6
-4w = 3 + -6

Combine like terms: 3 + -6 = -3
-4w = -3

Divide each side by '-4'.
w = 0.75

Simplifying
w = 0.75

See similar equations:

| q-6=6 | | 4=m-2 | | 12+g=16 | | t+15=19 | | sqrt(3x+2)=xsqrt(2) | | 12=((-3+1)(-3+1))(k) | | =x^4-6x^3+13*x^2-12*x+5 | | 0.5x(x-3)=54 | | x=2(6+2x)+8x | | 8x-20=2x-8 | | A=5*5*5(3.5) | | w+3/4=6 | | 3x+2=x^2-2 | | px^2-6x+p=0 | | 2x-36+x=90 | | 3x=2+5 | | 3j-9=6 | | 4x^2y-6xy^2=u | | 3x+x+2+4=18 | | x^2+x^2=c | | 9m-9=-45 | | x^2*X^2=c^2 | | C=(3C+5)+(4C-8) | | 12-x=4(x+13) | | 2(7x+1)=3(x+8) | | 4(x+1)=8(8-x) | | 9x-5=8x-0 | | 93-49= | | 5(y+-3)=20 | | 6d=(12-6) | | ln(500+x)=0 | | 4(m+6)-3(2m+1)=2(4m+7)+17 |

Equations solver categories